Recurrent lower motor neuron type facial palsy: an unusual manifestation of SLE. (2nd February 2011) - Gupta, Durgesh Kumar; Atam, Virendra; Chaudhary, S C
Abstract : Facial nerve palsy is the most common cause of mononeuropathy in the humans, Bell's palsy being the commonest cause of that. Cranial neuropathy, particularly facial is a rare event in systemic lupus erythematosus (SLE). The authors hereby report on a 20-year-old female patient who had recurrent lower motor neuron type facial palsy and on subsequent workup she was diagnosed as a case of SLE. She was put on oral prednisolone to which she showed gradual response. The authors believe that this is the first case report of SLE presenting as recurrent facial palsy.